Pengembangan Desain Kemasan Pupuk Untuk Meningkatkan Daya Saing Di Desa Mekar Sari - Putra, Giri Asvian; Wiraguna, Depri; Saputra, Zony Hendra; Azhari, Diah; Nur’aini, Hesti; Fariadi, Herri (Jurnal Dehasen Mengabdi, 2025)
Mekar Sari Village, located in Kabawetan District, Kepahiang Regency, has local resources such as organic fertilizer and cow milk that have not been fully optimized. One of the main challenges is the product packaging design, which is unattractive and lacks informativeness, affecting the product’s market appeal and competitiveness. This study aims to develop an innovative packaging design for organic fertilizer to enhance its appeal and product identification. The community service results show that the new packaging design, which incorporates visual elements such as logos, benefit descriptions, and fertilizer ingredients, can increase market interest and strengthen product image. Furthermore, farmers' involvement in the design process has raised market awareness of the sustainability of organic products. Although there are some challenges related to access to technology, this program is expected to contribute to local economic development and enhance product competitiveness in a broader market.